2022
DOI: 10.1136/jitc-2021-004424
|View full text |Cite
|
Sign up to set email alerts
|

Dual checkpoint targeting of B7-H3 and PD-1 with enoblituzumab and pembrolizumab in advanced solid tumors: interim results from a multicenter phase I/II trial

Abstract: BackgroundAvailability of checkpoint inhibitors has created a paradigm shift in the management of patients with solid tumors. Despite this, most patients do not respond to immunotherapy, and there is considerable interest in developing combination therapies to improve response rates and outcomes. B7-H3 (CD276) is a member of the B7 family of cell surface molecules and provides an alternative immune checkpoint molecule to therapeutically target alone or in combination with programmed cell death-1 (PD-1)–targete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 31 publications
2
55
0
Order By: Relevance
“…One treatment-related death occurred (pneumonitis). Objective responses occurred in 6 of 18 (33.3% [95% CI 13.3 to 59.0]) patients with checkpoint inhibitor (CPI)-naïve HNSCC and in 5 of 14 (35.7% [95% CI 12.8 to 64.9]) patients with CPI-naïve NSCLC [ 178 ]. This phase I/II trial showed that combining Enoblituzumab with Pembrolizumab demonstrated acceptable safety and effect in patients with CPI-naïve HNSCC and NSCLC.…”
Section: B7-h3mentioning
confidence: 99%
“…One treatment-related death occurred (pneumonitis). Objective responses occurred in 6 of 18 (33.3% [95% CI 13.3 to 59.0]) patients with checkpoint inhibitor (CPI)-naïve HNSCC and in 5 of 14 (35.7% [95% CI 12.8 to 64.9]) patients with CPI-naïve NSCLC [ 178 ]. This phase I/II trial showed that combining Enoblituzumab with Pembrolizumab demonstrated acceptable safety and effect in patients with CPI-naïve HNSCC and NSCLC.…”
Section: B7-h3mentioning
confidence: 99%
“…It was also reported that downregulated B7-H3 can reduce lipid synthesis via the SREBP-1/FASN signaling pathway in lung cancer [ 125 ]. T cells expressing B7-H3-specific chimeric antigen receptors (CARs) and bispecific killer cell engager (BiKE)-redirected NK cells have shown significant antitumor activity in a preclinical model [ 126 ], and combined targeting of B7-H3 and PD-1 has resulted in promising response rates in clinical trials [ 127 ].…”
Section: B7-h3 In Different Malignanciesmentioning
confidence: 99%
“…CD3 + T cell and B7-H3 bispecific antibodies and B7-H3-targeting CAR-T therapy have shown potent antimelanoma activity when investigated using in vivo and in vitro models [ 147 , 148 ], validating the great potential of B7-H3 in melanoma immunotherapy. Nevertheless, mechanistic studies and preclinical success have not yet been translated into a clinical benefit, and a poor response rate was observed in patients with melanoma who were treated with anti-B7-H3 and anti-PD-1 antibodies [ 127 ]. Clinical evaluations of multiple modalities in a larger cohort are still ongoing.…”
Section: B7-h3 In Different Malignanciesmentioning
confidence: 99%
“…Additionally, the potential value of various new inhibitory immune checkpoints (BTLA [130][131][132], B7 family [133][134][135][136][137], IDO-1 [138,139], LAG-3 [140,141]) and costimulatory molecules (GITR [142][143][144][145], ICOS [146][147][148], OX40 [149][150][151], 4-1BB [152][153][154], CD40 [155,156], CD27 [157][158][159]) has been confirmed for melanoma treatments. The efficacy and safety of some inhibitory checkpoints and costimulatory molecules in melanoma treatments, alone or combined with ICIs, have been preliminarily elucidated in early clinical trials [160][161][162][163][164][165][166][167][168][169][170][171][172][173] and others are in progress (NCT04773951, NCT04137900, NCT02554812). Currently, no large-sample study comparing the expression levels of these immune checkpoints in AM and CM tissues is available.…”
Section: Novel Immune Checkpointsmentioning
confidence: 99%